Crown Financial Asset Management: Objectives and Practice - Arthur Grimes (New Zealand Government, The Treasury, 2001)
This paper analyses key issues that may be relevant to setting the Crown's overall objectives and practices for financial asset and liability management. It examines implications of the nature of the Crown's balance sheet for asset and liability management and investigates the appropriate approach of the Crown towards managing risk (concluding that a risk averse approach is warranted). The issue of centralisation versus decentralisation of Crown asset and liability management is analysed both from a portfolio management perspective and from an organisational design perspective. Insights from private sector financial conglomerates are also incorporated. The paper concludes that individual Crown financial entities should each continue to be responsible for setting their own strategic asset allocation, after taking into account the nature of their liabilities. A central Crown body should, however, monitor and aggregate information from each of these entities and be delegated the responsibility and power to manage risks to the overall Crown balance sheet.
Keywords: H11; H63; 330; Crown balance sheet; Public debt management